Effects of Dynamic Hyperinflation on Left Ventricular Diastolic Function in Healthy Subjects — A Randomized Controlled Crossover Trial - Urban, Matthias Helmut; Mayr, Anna Katharina; Schmidt, Ingrid; Grasmuk-Siegl, Erwin; Burghuber, Otto Chris; Funk, Georg-Christian (Frontiers in Medicine, 2021)
OObjective: Diastolic dysfunction of the left ventricle is common in patients with chronic obstructive pulmonary disease (COPD). Dynamic hyperinflation was has been suggested as one a key determinant for of reduced diastolic function in COPD. We aimed to investigate the effects of induced dynamic hyperinflation on left ventricular diastolic function in healthy subjects to exclude other confounding mechanisms associated with COPD. Design: In this randomized controlled crossover trial (NCT03500822, https://www.clinicaltrials.gov/), we induced dynamic hyperinflation by using the validated method of Expiratory Resistance Breathingexpiratory resistance breathing (ERB), combining which combines tachypnea with expiratory resistance, , and compared the results to those ofcompared to tachypnea alone. Healthy male subjects (n=14) were randomly assigned to the ERB or control group with a subsequent crossover. Mild, moderate and severe hyperinflation (i.e. ERB1, ERB2, ERB3) was were confirmed by intrinsic positive end-expiratory pressure (PEEPi) using an esophageal balloon catheter. The effects on diastolic function of the left ventricle were measured by transthoracic echocardiographic assessment of the heart rate-adjusted transmitral E/A-ratio and E/e'-ratio. Results: We randomly assigned 7 participants to the ERB group and 7 to the control group (age 26 [24 to 26] versus 24 [24 to 34], p=0.81). Severe hyperinflation decreased the E/A-ratio compared to the controls control condition (1.63 [1.49 to 1.77] versus 1.85 [0.95 to 2.75], p=0.039), and moderate and severe ERB significantly increased the septal E/e'-ratio. No changes in diastolic function were found during mild hyperinflation. PEEPi levels during ERB were inversely correlated with the E/A- ratio (regression coefficient = -0.007, p=0.001). Conclusions: Our data indicate dynamic hyperinflation as a determinant of left ventricular diastolic dysfunction in healthy subjects. Therapeutic reduction of hyperinflation might be a treatable trait to improve diastolic function in patients with COPD.